New insights into the control of neurotrophic growth factor receptor signaling: Implications for nervous system development and repair - Alsina, Fernando Cruz (2012)
Neurotrophic growth factors control neuronal development by activating specific receptor tyrosine kinase positive signaling pathways, such as Ras-MAPK and PI3K-Akt cascades. Once activated, neurotrophic factor receptors also trigger a cascade of molecular events, named negative receptor signaling, that restricts the intensity of the positive signals and modulates cellular behavior. Thus, to avoid signaling errors that ultimately could lead to aberrant neuronal physiology and disease, negative signaling mechanisms have evolved to ensure that suitable thresholds of neuronal stimulation are achieved and maintained during right periods of time. Recent findings have revealed that neurotrophic factor receptor signaling is tightly modulated through the coordinated action of many different protein regulators that limit or potentiate signal propagation in spatially and temporally controlled manners, acting at specific points after receptor engagement. In this review, we discuss progress in this field, highlighting the importance of these modulators in axonal growth, guidance, neural connectivity, and nervous system regeneration.